Analysis of the Impact of CR and DAR on NPM at PT Bank BNI Tbk for the Period 2013-2023 - Wiharso, Gani; Basudani, Wahid Akbar (Dinasti Publisher, 2025)
This study aims to examine how the Current Ratio (CR) and Debt to Asset Ratio (DAR) influence the Net Profit Margin (NPM) of Bank Negara Indonesia (BNI) over the period from 2013 to 2023. The data used in this research consists of the bank's annual financial reports spanning 11 years, sourced internally from the bank. The research method applied is multiple linear regression analysis, with data processing carried out using SPSS software. The findings show that neither the Current Ratio nor the Debt to Asset Ratio significantly impacts the Net Profit Margin. The coefficient of determination is low (R² = 0.077), indicating that these two variables explain only 7.7% of the variation in Net Profit Margin. The F-test results also confirm that these variables do not have a significant collective effect on Net Profit Margin. Based on these results, it is recommended that BNI focus on other factors, such as cost control and operational efficiency, to enhance its profitability in the future.